An ink surgical marker pen is damaging to tendon cells. - Franklin, S; Jayadev, C; Poulsen, R; Hulley, P; Price, A (2012)
OBJECTIVES: Surgical marking during tendon surgery is often used for technical and teaching purposes. This study investigates the effect of a gentian violet ink marker pen, a common surgical marker, on the viability of the tissue and cells of tendon. METHODS: In vitro cell and tissue methods were used to test the viability of human hamstring explants and the migrating tenocytes in the presence of the gentian violet ink. RESULTS: The outcome of this study was that a constituent of the surgical marker pen causes cell and tissue death in culture, implying the same would occur in vivo. CONCLUSIONS: This is a cause for concern when marking tendon during surgical procedures, as it may compromise healing and repair and potentially contribute to a poor outcome. The authors suggest that an alternative surgical marking procedure should be found, or that all marker pens should undergo testing on human tendon tissue in vitro prior to use.